Recursos metodológicos para gestão do relacionamento com egressas/os da pós-graduação na Universidade Federal do Pará - FIGUEIREDO, Mônica de Souza (Universidade Federal do Pará, 2023)
The relationship between the alumni of postgraduate has become an emerging theme, stimulated, among other factors, by the valorization of indicators of social impact in national and international evaluations of higher education. This research presents the following guiding question: How to assist the coordinators and secretaries of the postgraduate programs from the Federal University of Pará (UFPA) to enhance the management actions of the relationship between the alumni students and their associated programs? To propose a solution to this questioning, the research aimed at developing methodological resources to assist in the relationship management with the alumni students from the postgraduate programs of UFPA. The theoretical background was based on the study of the history and the management of postgraduate programs in Brazil, as well as the scenario of postgraduate programs at UFPA. Another theoretical basis were the studies about the alumni students, specially referring to the relation between the alumni postgraduate students and their programs, and how this relationship can be fostered since the entrance period. From this discussion, it is proposed an initial conception from the term “alumni students’ relationship management”. In the same way, a survey about how UFPA currently holds the relationship management with the alumni students was carried out. In this diagnostic, it was clarified that the postgraduate programs are a complex scenario, and that the alumni students’ relationship management have been highlighted in the discussions about the management and the assessment of the postgraduate programs in Brazil, although the theme is incipient. Therefore, it is proposed two educational products composed by a set of methodological resources directed to coordinators and secretaries of postgraduate programs (as the first target audience of the research), for it to be used in the administrative, academic, and relationship management among the students (future alumni students) and alumni students. The methodological approach adopted was composed by bibliographical and documental research, state-of-the-art, the target audience profile survey, and a survey containing the information about the relationship with the alumni students in the reports of Coleta CAPES 2020 of the postgraduate programs of UFPA. The validation/co-creation of the product was realized through six sections, with groups of two or three participants each, totalizing 15 collaborators, who discussed all the educational product’s components. For the development of the methodological resources that compose the product, it was established four timeframes: the entrance, the middle way, the conclusion, and the alumni. As a result, it was elaborated a methodological matrix, with assessment criteria for each timeframe, that can be used by postgraduate programs for the relationship management with their students and alumni students. As a proposal for the matrix application, it is indicated the use of graphics as the “wheel of life” type, in which it is summarized the evaluative aspects and allows a diagnosis for the program and a self-evaluation to the student/alumni student. The second product is a strategies catalogue to the relationship management with the alumni students, with guidelines for actions to the creation and maintenance of relation with the alumni students. For a better diagnosis and selection of strategies to be applied, it is attached to the product a perception graphic of the relationship with the alumni students. It is expected this product to be an aggregator component for the postgraduate programs and to foster the collaborative and integrated work of management between coordinators and secretaries of postgraduate programs.